An Archaeological-Genealogical Analysis of Public Health Discourse on Lead: Reformulating Lead-based Paint as a Problem in Canada - O'Grady, Kelly (Université d'Ottawa / University of Ottawa, 2011)
Lead is a serious developmental neurotoxin with the capacity to interrupt brain development and impair functioning. Since at least 1930 numerous case studies in American, Canadian and Australian literature have identified lead based paint in the home as a source of poisoning for young children; and since at least 1990 evidence has shown that it is the lead dust from deteriorating paint in older homes and renovating activities that is the primary source of chronic exposure for young children today. Not much is known about the extent of childhood lead poisoning in Canada. Gaps in our understanding include a lack of national survey data on childhood blood lead levels and an absence of reliable data to determine the era of housing that poses the greatest risk. This thesis posits that despite this paucity of research knowledge there is evidence to suggest that populations of vulnerable children continue to be harmed by exposure to historic sources of lead, such as lead-based paint found in older housing stock. This thesis examines the evidence to support this contention by critically analyzing the Canadian public health response to the issue of childhood lead poisoning. Specific attention is paid to discourse corresponding to lead-based paint, the putative major pathway of exposure for children ages 1 to 5 years. Using Foucault’s genealogical/archaeological approach, as elaborated upon by Rawlinson (1987) this thesis discusses the socio-political and economical processes that shaped health care knowledge regarding childhood lead poisoning in Canada and influenced the way knowledge was produced and used by health care providers and policy makers. The analysis is assisted via a comparison of Canadian public health discourse with American discourse, with an emphasis on discourse appearing in the post leaded gasoline era (1990-2008). The strength of a Foucauldian archaeological/genealogical analysis for nursing research and particularly for this analysis is in its focus on discourse, surfaces of emergence, transformations, mutations, contingencies, events, recognition of power/knowledge strategies, descriptions of discipline technologies and consequences, and suggested possibilities of resistance. This thesis proposes that surveillance data constituted both a product and acatalyst of the dominant view on childhood lead poisoning occurring from residential sources and posits that a lack of Canadian context specific surveillance data was the major “policing” factor limiting Canadian public health discourse. Further, privileged access to blood lead survey data maintained the view that childhood lead poisoning was a problem of the past or an American problem. Third, tensions among Canada’s two federal agencies which hold primary responsibility for lead, health and housing resulted in a weakened response whereby, to date, no legislation exists to protect vulnerable populations of Canadian children from exposure to historic sources of lead in residential dwellings.
Keywords: lead poisoning; Canada; child; environment; health; public health; housing; Foucault; critical discourse analysis